CHEMICAL COMPOSITION OF THE SEEDS OF SOME Medicago SPECIES - Kokten, Kagan; Bakoglu, Adil; Kocak, Alpaslan; Bagci, Eyup; Akcura, Mevlut; Kaplan, Mahmut (Springer, 2011)
[Abstract Not Available]
Keywords: Fatty-Acid-Composition; Patterns; Turkey; Oils